1998
DOI: 10.1093/ajcn/67.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of low bone density with a gluten-free diet in children and adolescents with celiac disease

Abstract: Osteoporosis is a common finding in adult celiac disease patients; however, there are still few data regarding children and adolescents. In the present study we measured the bone mineral density (BMD) in children and adolescents at diagnosis of celiac disease and after approximately 1 y of a gluten-free diet. BMD was measured at the lumbar spine and in the whole skeleton by dual-energy X-ray absorptiometry in 44 celiac disease patients aged 2.58-20.42 y at diagnosis. BMD was also measured in a subset of 25 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0
16

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 38 publications
4
89
0
16
Order By: Relevance
“…Effect of gluten-free diet C Tau et al of those who were older at the time of diagnosis and treatment. Mora et al (1998) found spine and whole-body BMD of children with celiac disease to increase 0.06 g/cm 2 and 0.05 g/cm 2 , respectively, after 1.470.04 years on GFD. According to these authors, BMD was normal at the end of the study.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Effect of gluten-free diet C Tau et al of those who were older at the time of diagnosis and treatment. Mora et al (1998) found spine and whole-body BMD of children with celiac disease to increase 0.06 g/cm 2 and 0.05 g/cm 2 , respectively, after 1.470.04 years on GFD. According to these authors, BMD was normal at the end of the study.…”
Section: Discussionmentioning
confidence: 86%
“…BMD has been found to increase after GFD in adults, without reaching normal values (Mautalen et al, 1997). Although several studies have assessed bone mass in children with celiac disease (Exner et al, 1978;Mora et al, 1993;Scotta et al, 1997;Mora et al, 1998Mora et al, , 1999Rea et al, 1998;Muzzo et al, 2000), most of them comprised a population of older patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis et al (35) observed that years of exposure to gluten before diagnosis of CD do not appear to influence BMD significantly. The relationship between GFD and bone restoration seems to be more pronounced in paediatric population (36,37): one year long GFD did not improve BMD in adult population according to the previously mentioned Irish study (23).…”
Section: Discussionmentioning
confidence: 91%
“…[8][9][10] In contrast, other studies showed that an impaired skeletal development during childhood may be largely reversible when treating underlying diseases. [11][12][13] Age-and sex-specific bone reference values can help to assess skeletal development during childhood and to compare the bone health status of a child with that of a healthy population having the same age, sex and ethnicity. Thus, deviations from a normal skeletal development may be identified in an early stage.…”
Section: Introductionmentioning
confidence: 99%